2014
DOI: 10.1155/2014/192072
|View full text |Cite
|
Sign up to set email alerts
|

Interval Estimation of Stress-Strength Reliability Based on Lower Record Values from Inverse Rayleigh Distribution

Abstract: We consider the estimation of stress-strength reliability based on lower record values when and are independently but not identically inverse Rayleigh distributed random variables. The maximum likelihood, Bayes, and empirical Bayes estimators of are obtained and their properties are studied. Confidence intervals, exact and approximate, as well as the Bayesian credible sets for are obtained. A real example is presented in order to illustrate the inferences discussed in the previous sections. A simulation study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Birnbaum (1956), Gupta (2005, 2006), Razaei, Tahmasbi, andMahmoodi (2010), Hussian, (2013) studied the estimation of R for different distributions. The recorded values and more studies about R with different distributions and different methods of estimation found in Baklizi (2008Baklizi ( , 2014, Essam (2012), Tarvirdizade, and Kazemzadeh Garehchobogh (2014).…”
Section: Introductionmentioning
confidence: 96%
“…Birnbaum (1956), Gupta (2005, 2006), Razaei, Tahmasbi, andMahmoodi (2010), Hussian, (2013) studied the estimation of R for different distributions. The recorded values and more studies about R with different distributions and different methods of estimation found in Baklizi (2008Baklizi ( , 2014, Essam (2012), Tarvirdizade, and Kazemzadeh Garehchobogh (2014).…”
Section: Introductionmentioning
confidence: 96%
“…The survival probability of stress-strength R = P(Y < X) based on record values is considered in Baklizi [6] for generalized exponential distribution. Subsequent papers extended this work assuming various lifetime distributions for stress-strength random variables, for instance, in Baklizi [7,8,9], for one and two parameter exponential distribution, Essam [10] for type I generalized logistic distribution, Baklizi [11] for two-parameter Weibull distribution, Tarvirdizade and Kazemzadeh Garehchobogh [12] for inverse Rayleigh distribution, Al-Gashgari and Shawky [13] for exponentiated Weibull distribution, Hassan et al [14] for exponentiated inverted Weibull distribution and Hassan et al [15] for generalized inverted exponential distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Also, authors found Bayesian analysis for record data Based on Generalized Inverted Exponential Model which considered in [3]. For finding interval estimation for Inverse Rayleigh Distribution based on lower record see [4]. For estimating the reliability for a family of life time distribution based on records see [5].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2: MSEs OF MLE AND BAYES ESTIMATORS WHEN R=0.75 Shows that the MSEs of MLE and BAYES estimators decrease as n and m are increase at R=0.75, also, MSEs of MLE is smallest than MSEs of BayesFor Real data figures[3,4] …”
mentioning
confidence: 99%